Higher Education in South East Asia - Indonesia - Nizam, Nizam (UNESCO Asia and Pacific Regional Bureau for Education, 2006)
South-East Asian countries share many commonalities, yet their political, cultural, socio-economic and environmental conditions are also rich in diversity. Likewise, higher education in the region stems from different historical backgrounds and has undergone various kinds of challenges and various stages of development. The rapid expansion of student enrolment, the knowledge explosion, advances in information and communication technology, globalization, economic restructuring, and financial constraints have all contributed to higher education reforms in these countries and resulted in varied outcomes. Based on a sense of “unity in diversity,” many higher education policy makers and practitioners in the region believe that their higher education systems can benefit from closer cooperation and exchange of lessons learned.